Decision making process and factors contributing to research participation among general practitioners: A grounded theory study - Tong, Seng Fah; Ng, Chirk Jenn; Lee, Verna Kar Mun; Lee, Ping Yein; Ismail, Irmi Zarina; Khoo, Ee Ming; Tahir, Noor Azizah; Idris, Iliza; Ismail, Mastura; Abdullah, Adina (Public Library of Science, 2018)
Introduction The participation of general practitioners (GPs) in primary care research is variable and often poor. We aimed to develop a substantive and empirical theoretical framework to explain GPs’ decision-making process to participate in research. Methods We used the grounded theory approach to construct a substantive theory to explain the decision-making process of GPs to participate in research activities. Five in-depth interviews and four focus group discussions were conducted among 21 GPs. Purposeful sampling followed by theoretical sampling were used to attempt saturation of the core category. Data were collected using semi-structured open-ended questions. Interviews were recorded, transcribed verbatim and checked prior to analysis. Open line-by-line coding followed by focus coding were used to arrive at a substantive theory. Memoing was used to help bring concepts to higher abstract levels. Results The GPs’ decision to participate in research was attributed to their inner drive and appreciation for primary care research and their confidence in managing their social and research environments. The drive and appreciation for research motivated the GPs to undergo research training to enhance their research knowledge, skills and confidence. However, the critical step in the GPs’ decision to participate in research was their ability to align their research agenda with priorities in their social environment, which included personal life goals, clinical practice and organisational culture. Perceived support for research, such as funding and technical expertise, facilitated the GPs’ participation in research. In addition, prior experiences participating in research also influenced the GPs’ confidence in taking part in future research. Conclusions The key to GPs deciding to participate in research is whether the research agenda aligns with the priorities in their social environment. Therefore, research training is important, but should be included in further measures and should comply with GPs’ social environments and research support.